2015
DOI: 10.1080/15384047.2015.1071732
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hepaCAM inhibits bladder cancer cell proliferation via a Wnt/β-catenin-dependent pathwayin vitroandin vivo

Abstract: Keywords: bladder cancer, HepaCAM, T24, Wnt/b-catenin Abbreviations: Ad, adenvirus; HepaCAM, hepatocyte cell adhesion molecule.We previously established that hepatocyte cell adhesion molecule (hepaCAM), a typical structure of immunoglobulin (Ig)-like adhesion molecules, inhibited the proliferation and the progression of cultured human bladder cancer cells. As increasing evidence reveals that aberrant activation of canonical Wnt pathway is involved in the pathogenesis of bladder cancer, and b-catenin serves as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…MMP-2 is an enzyme that has been implicated in the malignant progression of BCa (44). Usually, β-catenin, c-myc, and MMP-2 have a synergistic effect on BCa tumorigenesis and progression (39,45). In the present study, the suppression of CXCR4 expression also decreased the protein expression of β-catenin targeting genes (MMP-2 and c-myc).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…MMP-2 is an enzyme that has been implicated in the malignant progression of BCa (44). Usually, β-catenin, c-myc, and MMP-2 have a synergistic effect on BCa tumorigenesis and progression (39,45). In the present study, the suppression of CXCR4 expression also decreased the protein expression of β-catenin targeting genes (MMP-2 and c-myc).…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies indicated that β-catenin may be a biomarker for the metastatic progression of BCa patients and that it was associated with poor patient survival (37,38). Wnt/β-catenin signaling has been shown to be frequently involved in various signaling pathways related to cell proliferation and metastasis in BCa (39,40). For example, hepatocyte cell adhesion molecule (hepaCAM) specifically suppressed β-catenin expression during BCa cell proliferation (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CTNNB1 is highly expressed in RT4 cells and expressed in lower amounts in ScaBER cells, which is similar to the expression pattern of TLE2. The activation of the Wnt/β-catenin signaling pathway plays an important role in tumorigenesis and development of various cancers including BLCA [30][31][32]. Gain-of-function mutations in CTNNB1 are detected in numerous human cancers [33][34][35]; therefore, it is necessary to explore the role of Wnt/β-catenin regulated genes in BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when expressed in MCF-7 breast cancer cells, GlialCAM increases cell motility and adhesion, decreases proliferation, and induces p53-mediated cellular senescence [ 279 , 283 ]. GlialCAM inhibits proliferation and β-catenin signalling in bladder carcinoma cells [ 284 , 285 ]. Furthermore, in renal carcinoma cells, GlialCAM decreases proliferation, induces cell cycle arrest, and stimulates c-Myc degradation [ 286 ].…”
Section: − Channelsmentioning
confidence: 99%